Hubungan Kepatuhan Instruksi Kerja Dengan Perilaku Aman Pada Karyawan Bagian Mekanik PT. Indo Acidatama Tbk Kemiri Kebakkramat Karanganyar - Aisyah, Siti Nur (2016)
Work instructions were work orders that arranged squentially to guided and facilitated the implementation of a job that had work related to the work tools, mechanical hazards, danger of mechanical, chemical hazards, physical hazards and biological hazards is a type of job that required working instructions. PT. Indo Acidatama Tbk, Kemiri, Kebakkramat, Karanganyar used work instructions to control environmental, personal protective equipment and work procedures. The purpose of this study was to analyze the relationship work instructions complianced with safe behavior on the part of employees of mechanical PT. Indo Acidatama Tbk, Kemiri, Kebakkramat, Karanganyar. The method used analytic survey with cross sectional approach. Techniques of gets the sample used total sampling method with 30 respondences. The result of this study used the Pearson Product Moment showed P value was 0.017 (P <0.05) and the correlation value of 0.432, which means there was a significant relationship with a moderate level of correlation between the Compliance work instructions with the safe behavior on the part of employees of mechanical PT. Indo Acidatama Tbk, Kemiri, Kebakkramat, Karanganyar. This study concluded that the employees adhere to the instruction of work the employees is more secure behavior of the operation and vice versa.